METODE ISTIDLAL DAN ISTISHAB (FORMULASI METODOLOGI IJTIHAD) - Umar Muhaimin (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2017)
Ra’yu (logic) is an important aspect of ijtihad thus in ushul fiqh - a subject discussing the process of ijtihad – there are several method of finding the law based on logic of fuqaha (scholars), some of them are istishhab and istidlal (finding the sources). Those are two sides of a coin which are two inseparable methods of ijtihad. The source (dalil) is a material object while istidlal is a formal object. Generally, istidlal refers to finding sources either from Qur’an, Sunna (Tradition), or al Maslahah (considerations of public interest) by means of muttafaq (settled methods) such as Qur’an, Sunna (Tradition),  Ijma’ (consensus), Qiyas (analogy) or mukhtalaf (debatable methods) such as Mazhab ash-shahabi (fatwa of a companion), al-‘urf (custom), Syar’u Man Qablana (revealed laws before Islam), istihsan (equity), istishab (presumption of continuity)  or sad al-dzariah (blocking the means). Al-Syatibi classified four mind sets of understanding nash (the Text) i.e. zahiriyah (textual), batiniyat (esoteric), maknawiyat (contextual) and combination between textual and contextual.